Musik bukan Pekerjaan: Distingsi dan Transgresi dalam Karier Bermusik Musisi Metal Ekstrem Yogyakarta - Agustinus Aryo Lukisworo; Oki Rahadianto Sutopo (Universitas Gadjah Mada, 2021)
This article focuses on the separation between music and work that has been done by Yogyakarta’ extreme metal musician. Along with a deeper explanation of youth cultural practices in Yogyakarta, this article also provides a gap bridge between youth culture and youth transition perspective. In order to obtain those purposes, this article utilizes youth culture perspective and youth transition perspective approach, together with field and doxa. Regarding the research method, this article uses qualitative ethnographic approach and has been done through six months data collecting. This research approach was chosen in order to capture the concrete reality that has been experienced by research informants. Based on the findings analysis, which has been done both textually and interpretively, the separation between music and work among informants, on the one hand could be understood as a strategy to maintain informants' pride within the extreme metal scene. On the other hand, this separation also could be defined as a strategy to maintain informants' social position, especially as Indonesian middle class.